PENYELESAIAN WANPRESTASI DARI PEMBAYARAN KREDIT DI LPD DESA PAKRAMAN LEBIH GIANYAR - Nyoman Arnawa, I Gusti Ngurah; -, Adiwati; Mudana, I Nyoman (Kertha Desa; Vol. 01, No. 01, Maret 2013, 2013)
Village Credit Institutions is belong of custom village that specified in the awig-awig and perarem of custom village. In return of credit at Credit Institutions village, people more tend to pay off all their loans in the Village Credit Institutions rather than custome penalized because according to their that custom sanctions they will faced by the public. And if the Village Credit Institutions difficulty in collecting the loan hence the Village Credit Institutions will bestow to the custom village. Customary sanctions to be awarded it depends on from the result of custom village meeting which may in the form of seizure of the wealth of the borrower's credit, and others.
Keywords: Village Credit Institution,credit,customsanctions.